Analisis Efikasi Diri Aparatur Sipil Negara berdasarkan Perspektif Lintas Generasi dan Gender di Era Transformasi Birokrasi - Perdhana Ari Sudewo; Syifa Kamila Defayani (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2026)
Self-efficacy plays a critical role in supporting bureaucratic transformation among Indonesian civil servants, which increasingly demands adaptability and innovation. This study aims to examine differences in self-efficacy across generational cohorts (X, Y, and Z) and gender. A comparative quantitative approach was employed, using stratified random sampling based on generational and gender categories. The findings reveal significant differences in self-efficacy across generations and gender. Generation X demonstrated the highest level of self-efficacy, followed by Generation Z, while Generation Y showed the lowest. Male civil servants reported higher self-efficacy than their female counterparts. Interaction analysis further indicated that males from Generation Z and females from Generation X exhibited the highest self-efficacy within their respective groups. Actionable recommendations highlight the importance of generation- and gender-sensitive human resource development, strengthening mentoring and coaching systems, and broadening work experiences through job rotation and cross-functional collaboration to enhance self-efficacy. This study contributes to the organizational psychology literature by providing a cross-generational and gender-based perspective within the context of Indonesian civil servants and offers more targeted policy implications for public sector human resource development.